Resveratrol downregulates TNF-α-induced monocyte chemoattractant protein-1 in primary rat pulmonary artery endothelial cells by P38 mitogen-activated protein kinase signaling - Lin JW; Yang LH; Ren ZC; Mu DG; Li YQ; Yan JP; Wang LX; Chen C (Dove Medical Press, 2019)
Jian-Wei Lin,1 Le-He Yang,2 Zhuo-Chao Ren,3 De-Guang Mu,3 Ya-Qing Li,3 Jian-Ping Yan,3 Liang-Xing Wang,4 Chun Chen31Department of Cardiology, Xiasha Campus, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Hangzhou 310018, Zhejiang, People’s Republic of China; 2Department of Respiratory Medicine, Wenzhou Medical University, Wenzhou 325600, Zhejiang, People’s Republic of China; 3Department of Respiratory Medicine, Zhejiang Provincial People’s Hospital, People’s Hospital of Hangzhou Medical College, Hangzhou 310014, Zhejiang, People’s Republic of China; 4Department of Respiratory Medicine, The First Affiliated Hospital, Wenzhou Medical University, Wenzhou 325000, Zhejiang, People’s Republic of ChinaBackground: To evaluate the effects of resveratrol to monocyte chemoattractant protein-1 (MCP-1) and the role of p38 mitogen-activated protein kinase (MAPK) in this process in vitro.Materials and methods: Animal acute pulmonarythromboembolism (PTE) model: rat model was established by infusion of an autologous blood clot into the pulmonary artery through a polyethylene catheter. One hundred and thirty-two rats were randomly and equally divided into ten groups: rats-control (untreated), rats-1% DMSO, rats-TNF-α, rats-TNF-α + resveratrol, rats-TNF-α +C1142, rats-TNF-α+SB203580, rats-TNF-α+resveratrol + SB203580, rats-resveratrol only, rats-C1142 only, and rats-SB203580 only. Rat pulmonary artery endothelial cells (RPAs) tests: RPAs were isolated from above animal and designated as: RPAs-control, RPAs-1% DMSO control, RPAs-TNF-α, RPAs-TNF-α + resveratrol, RPAs-TNF-α + C1142, RPAs-TNF-α + SB203580, RPAs-TNF-α + resveratrol + SB203580, RPAs-resveratrol only, RPAs-C1142 only, and RPAs-SB203580 only. Each group was further divided into 1, 4, and 8 hrs time point for evaluation (n=6 rats per time point) except RPAs-TNF-α + SB203580, RPAs-TNF-α + resveratrol + SB203580, RPAs-C1142 and RPAs-SB203580 only, which were evaluated at 8 hrs time point. At each time point, mRNA and protein expressions of RPAs of MCP-1 were measured. The phosphorylation of p38 MAPK (p-pMAPK) of RPAs was also detected.Results: We found that the RPAs-TNF-α elicited significant increases in MCP-1 expression and phosphorylation of p38 mitogen-activated protein kinase (p-p38 MAPK). Furthermore, the MCP-1 expressions of RPAs-Resveratrol, RPAs-C1142, and RPAs-SB203580 were significantly down-regulated, which was associated with robustly suppressed TNF-α-induced p-p38MAPK expression.Conclusion: Our findings suggested that MCP-1 was involved in the formation of TNF-α-induced inflammatory response, and resveratrol could down-regulate the expression of MCP-1 via TNF-α- inhibition, which might contribute to the decline of acute PTE-induced PH in vivo.Keywords: inflammation, pulmonary artery endothelial cells, pulmonary hypertension, pulmonary thromboembolism, resveratrol